Optimal design of high efficiency double helical gear based on dynamics model - Fengxia Lu (SN Applied Sciences, 2021)
Abstract A 16-degree-of-freedom dynamic model for the load contact analysis of a double helical gear considering sliding friction is established. The dynamic equation is solved by the Runge–Kutta method to obtain the vibration displacement. The method combines the friction coefficient model based on the elastohydrodynamic lubrication theory with the dynamic model, which provides a theoretical basis for the calculation of the power loss of the transmission system. Moreover, the sensitivity analysis of the parameters that affect the transmission efficiency is carried out, and an optimization method of meshing efficiency is proposed without reducing the bending strength of the gears. This method can directly guide the design of the double helical gear transmission system.